Noncontinuous Super‐Diffusive Dynamics of a Light‐Activated Nanobottle Motor. (24th April 2018) - Xuan, Mingjun; Mestre, Rafael; Gao, Changyong; Zhou, Chang; He, Qiang; Sánchez, Samuel
Abstract: We report a carbonaceous nanobottle (CNB) motor for near infrared (NIR) light‐driven jet propulsion. The bottle structure of the CNB motor is fabricated by soft‐template‐based polymerization. Upon illumination with NIR light, the photothermal effect of the CNB motor carbon shell causes a rapid increase in the temperature of the water inside the nanobottle and thus the ejection of the heated fluid from the open neck, which propels the CNB motor. The occurrence of an explosion, the on/off motion, and the swing behavior of the CNB motor can be modulated by adjusting the NIR light source. Moreover, we simulated the physical field distribution (temperature, fluid velocity, and pressure) of the CNB motor to demonstrate the mechanism of NIR light‐driven jet propulsion. This NIR light‐powered CNB motor exhibits fuel‐free propulsion and control of the swimming velocity by external light and has great potential for future biomedical applications.